1984
DOI: 10.1112/blms/16.4.421
|View full text |Cite
|
Sign up to set email alerts
|

A Note on Gaps between Zeros of the Zeta Function

Abstract: Recently Montgomery and Odlyzko [1] showed, assuming the Riemann Hypothesis, that infinitely often consecutive zeros of the zeta function differ by at least 1.9799 times the average spacing and infinitely often they differ by at most 0.5179 times the average spacing. We improve their result by a better choice of a certain weight function which occurs in their proof and we give explicit bounds for what is possible by this method. In addition, we indicate a method of proof which is considerably simpler than that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 0 publications
3
74
0
Order By: Relevance
“…In fact, it is known that this is not attainable using Montgomery and Odlyzko's method with Dirichlet polynomials of length ≤ T . Specifically, in [2], it is shown that h(c) < 1 if c < We have not been able to prove that our bounds for λ and μ in Theorem 1.1 are the optimal bounds for our choice of coefficients {a ± k } in (2.2). In the special case of r = 1, this optimization problem has been solved (in terms of prolate spheroidal wave functions).…”
Section: Numerical Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, it is known that this is not attainable using Montgomery and Odlyzko's method with Dirichlet polynomials of length ≤ T . Specifically, in [2], it is shown that h(c) < 1 if c < We have not been able to prove that our bounds for λ and μ in Theorem 1.1 are the optimal bounds for our choice of coefficients {a ± k } in (2.2). In the special case of r = 1, this optimization problem has been solved (in terms of prolate spheroidal wave functions).…”
Section: Numerical Calculationsmentioning
confidence: 99%
“…Very little is known unconditionally; however, Selberg (unpublished, but announced in [12]) has shown that μ < 1 < λ. Assuming the Riemann Hypothesis, numerous authors [2,5,7,8,10] have obtained explicit bounds for μ and λ. Theorem 1.1 improves the previously best known results under this assumption which were μ < 0.5172 due to Conrey, Ghosh, and Gonek [2] and λ > 2.6306 due to R. R. Hall [5]. The results in Hall's paper are actually unconditional, but a lower bound for λ can only be obtained if the Riemann Hypothesis is assumed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By a different method (on RH), Montgomery and Odlyzko [30] improved on this result and obtained the upper bound 0.5179. Conrey, Ghosh, and Gonek [5] later replaced this by 0.5172.…”
Section: Application To Simple Zeros and Small Gaps Between Zerosmentioning
confidence: 99%
“…To prove our theorem, we adapt a method developed by Conrey, Ghosh, and Gonek [3] on gaps between consecutive nontrivial zeros of ζ(s) in the interval [0, T ] for T large. The method is conditional on the Riemann Hypothesis.…”
Section: It Is Well Known Thatmentioning
confidence: 99%